2015
DOI: 10.1080/00036846.2015.1076146
|View full text |Cite
|
Sign up to set email alerts
|

Short selling and exchange-traded funds returns: evidence from the London Stock Exchange

Abstract: An exchange-traded fund (ETF) is a security that tracks a basket of stocks. An ETF investor gains immediate exposure to the basket, by taking either a long or short position on this instrument. Both hedgers and speculators can short ETFs, making the informational content of increases in ETF short interest difficult to interpret. Using high-frequency (daily) short-interest data for ETFs traded on the London Stock Exchange between June 2006 and April 2010, we examine the price impact on ETFs of increases in shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…While Lynch, et al (2014) focus on whether short selling predicts overall market direction, we focus on the relative performance of sectors. Our findings that contrarian strategies might be profitable extend the research of Mohamad, Jaafar, and Goddard (2016). They examine a measure of daily short interest for ETFs traded on the London Stock Exchange.…”
Section: Introductionsupporting
confidence: 70%
“…While Lynch, et al (2014) focus on whether short selling predicts overall market direction, we focus on the relative performance of sectors. Our findings that contrarian strategies might be profitable extend the research of Mohamad, Jaafar, and Goddard (2016). They examine a measure of daily short interest for ETFs traded on the London Stock Exchange.…”
Section: Introductionsupporting
confidence: 70%
“…An exchange traded fund (ETF) is a security that tracks a portfolio of stocks in the ETF’s benchmark index ( Mohamad, Jaafar, & Goddard, 2016 ). ETFs can act as investment tools characterized by low transaction costs and high intraday liquidity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Other researchers find inconsistencies in the overvaluation hypothesis. Mohamad et al (2016) find that high levels of short interest in ETFs are associated with over-performance. Best et al (2008) find that there are significant increases in short interest prior to large, negative returns, but they find even higher levels of short interest prior to large, positive returns.…”
Section: Introductionmentioning
confidence: 80%
“…High short interest levels help price efficiency by dampening the price inflation of the stock and stopping it from becoming too overvalued. Mohamad et al (2016) find evidence of high short interest leading to over-performance. Their study was of ETFs, and they suggested the results were due to hedging strategies.…”
Section: Literature Reviewmentioning
confidence: 87%